Tracing craniovascular traits in artificially modified pre‐Columbian crania from Cuba, the largest Caribbean archipelago. (29th December 2020) - Rangel‐de Lázaro, Gizéh
Abstract: The impressions left by the vascular system on the surface of the skull, like those of the middle meningeal vessels, the dural venous sinuses, and the emissary veins, are a unique source of vascular and anatomical evidence when working with osteological collections, as is the case with bioarchaeological, forensic, and paleoanthropological investigations. Craniovascular features have been investigated in multiple modern human populations; however, no information is available on their analysis in artificially modified pre‐Hispanic Caribbean skulls. To shed light on this matter, this report provides a reference for the prevalence, characterization, and distribution of craniovascular traits using a collection of fronto‐occipital tabular oblique artificially shaped pre‐Columbian crania from Cuba (the largest archipelago in the Caribbean) as a case study. Results suggest that changes produced by intentional head‐shaping may have affected the pattern and direction of endocranial vascular structures, whereas emissary foramina placed in less‐affected areas appear to be less influenced by changes in cranial morphology. Future work will investigate the consequences of artificial modification on the cranial and endocranial vascular systems and compare them with unmodified pre‐Columbian specimens. Also, the effects of head shaping in endocranial thermoregulation should be explored in the future. Providing new knowledge about the prevalence and variation of the craniovascular traits may be useful not only in research based on osteoarcheological collections but also in medicine.